Detecção e identificação genética de pestivírus de bovinos - Monteiro, Francielle Liz (2018)
he genus Pestivirus, belonging to the family Flaviviridae, comprises three viral species that infect cattle: bovine viral diarrhea virus 1 (BVDV-1)/Pestivirus A, BVDV-2/Pestivirus B and pestivirus HoBi-like (HoBiPeV)/Pestivirus H. The two BVDV species and HoBiPeV – as well as the respective subgenotypes – may be identified based on the comparison of sequences within the 5’ non-translated region (5’UTR) of the viral genome, which allows to group the isolates in twenty-one subgenotypes of BVDV-1 (1a-1u), four genotypes of BVDV-2 (2a–2d) and four of HoBi-like (-3a to -3d). The 5’UTR is also a target for molecular detection of pestiviruses due to its high conservation. In a first study, we describe the detection and genetic identification of pestiviruses present in 73 lots of fetal bovine serum (FBS) of Brazilian origin, produced between 2006 and 2014. Thirty-nine FBS batches (53.4%) were positive for pestivirus RNA. Thirty-four (46.6%) contained BVDV-1, being 23 -1a, eight -1b and three -1d. Six batches (8.2%) contained BVDV-2, two of them being -2a, three -2b and one of undetermined subgenotype. Four batches of FBS (5.5%) were contaminated with HoBiPeV and five batches (6.8%) contained more than one pestivirus. These results demonstrate the contamination of Brazilian origin FBS with pestivirus RNA. The second study reports the characterization of 90 pestiviruses obtained from serum samples from cattle in the state of Rio Grande do Sul for export in 2017, of which 38 BVDV-1 (42.2%), 31 BVDV-2 (34.4%) and HoBiPeV (23.4%). Of the BVDV-1 samples, only the 1a (n = 28, 31.1%) and -1b (n = 10, 11.1%) subgenotypes were identified. All 30 BVDV-2 isolates belonged to the -2b subgenotype and the 21 HoBiPeV viruses were grouped into subgroup 3a. The third study describes a new primer pair (BP189-389) for the detection of three bovine pestivirus species (BVDV-1, -2 and HoBiPeV). RT-PCR with primer 324-326 detected 110 positive samples, 62 for BVDV-1, 38 for BVDV-2 and 10 for HoBiPeV; and primer 90-368 detected 97 positive samples (64 BVDV-1; 33 BVDV-2). Primer specific for BVDV-2 detected 45 positive samples (including 38 detected by 324-326 and 33 by 90-368); while RT-PCR using the primer specific for HoBiPeV detected 26 positive samples (including 10 detected with 324-326). RT-PCR using primer BP189-389 detected all 135 samples, including the 26 HoBiPeV detected by N2-R5. Thus, primer BP189-389 demonstrated high sensitivity and specificity in the detection of BVDV-1, BVDV-2 and HoBiPeV and may be an alternative in the diagnosis of bovine pestiviruses. Summarizing, the present study presents contributions for the diagnosis of bovine pestiviruses and adds new information on the genetic profile of pestiviruses circulating in cattle from RS.